Formation and regulation of bicontinuous structured nanocomposites with interfacially jammed nanoparticles. (December 2022) - Zhang, Haimo; Zhong, Jun; Xu, Huilong; Shi, Xuanyu; Yang, Li; Sun, Shihao; Song, Yihu; Zuo, Min; Zheng, Qiang
Graphical abstract: Abstract: Bicontinuous structured nanocomposites with nanoparticles (NPs) assembled at the interface between two fluids have a wealth of proposed applications. Here, we used a universal and facile strategy to prepare such various bicontinuous stable nanocomposites filled with homopolymer-brush grafted NPs of various dimensions. We investigated the detailed formation of such nanocomposites online and proposed a model to fit and predict the effect of NPs at the interface on the domain coarsening of blend matrix and further stabilizing their bicontinuous morphology, based on the influence of NPs percolation on the time-dependent effective interfacial tension. The morphology evolution of nanocomposites can be predicted from the volume fraction of NPs, annealing time and temperature, which may provide some guidelines for the design and preparation of bicontinuous structured nanocomposites with the controllable and stable structure.